Decoding phenotypic signatures of Cylas formicarius Fab. resistance in a global sweetpotato (Ipomoea batatas [L.] Lam.) germplasm collection - Morales, Alfredo; Ma, Peiyong; Jia, ZhaoDong; Rodríguez, Dania; Vargas, Iván Javier Pastrana; González, Rosa Elena; Molina, Osmany; Jiménez, Alay; Rodríguez, Yuniel; Morales, Lilian; Beovides, Yoel; Portal, Orelvis; et al. (Frontiers in Plant Science, 2025)
IntroductionSweetpotato (Ipomoea batatas [L.] Lam.) is a critical global food crop that suffers devastating yield losses from the sweetpotato weevil (Cylas formicarius), especially in tropical regions where chemical control is often impractical. Breeding for stable resistance has been hindered by an insufficient characterization of reliable phenotypic markers across diverse genetic backgrounds.MethodsWe evaluated 731 accessions from Cuba’s national sweetpotato collection, enriched with global varieties, to identify morphological traits associated with natural resistance to C. formicarius. Resistance and susceptibility were assessed through combined field and laboratory bioassays.ResultsOnly 6.5% of the accessions demonstrated resistance (<10% infestation), while 80% were highly susceptible. Weak to moderate correlations linked resistance to smoother root surfaces (r = 0.31) and lighter flesh pigmentation (r = -0.38). The strongest correlation was observed with deeper tuberization (r = -0.72). Six Cuban genotypes combined agronomic viability (yield >10 t ha⁻¹) with resistance. Five of these employed deep tuberization as a physical escape mechanism, while one genotype, INIVIT B-25, exhibited shallow tuberization (mean depth 4.53 cm) yet maintained resistance, suggesting a biochemical defense strategy. Under controlled infestation, INIVIT B-2022 demonstrated the strongest antibiosis effect, suppressing adult emergence to just two individuals.DiscussionOur study decodes key phenotypic signatures of weevil resistance, providing immediately actionable morphological traits for use in Caribbean breeding programs. The discovery of a resistant genotype with shallow roots indicates the presence of a non-escape, potentially biochemical resistance mechanism. This highlights the critical need for subsequent molecular studies to uncover the complementary genetic and biochemical bases of these defenses.